2013
DOI: 10.4314/jae.v15i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Extension Systems in West Africa: Adoptable Strategies for Nigeria’s Agricultural Extension Reform Agenda

Abstract: National agricultural extension and advisory systems have undergone major changes during the past two decades. These changes have been attributed to the success of the Green Revolution, commercialisation of agriculture and trade liberalization. In addition, transnational corporations develop a wide range of new technologies, which directly impact on agricultural production in developed and developing countries. As more and more production technologies become "private goods" and as an increasing percentage of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This finding supported the observation of Nwachukwu (2013) who reported that different types of extension approaches were being practiced in various parts of the world and that each approach reflects a particular set of objectives, aims, clients and socio-cultural setting. The practice of extension today according to Akinola, Issa and Sanni (2011), is dissimilar in that the process is dominated by organizations, and its scope has extended from disjointed local events to a complicated, large scale and even worldwide activity. S -Significant at P < 0.05%…”
Section: Factors That Will Increase the Productivity Of Yam Farmers In Rivers And Imo Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supported the observation of Nwachukwu (2013) who reported that different types of extension approaches were being practiced in various parts of the world and that each approach reflects a particular set of objectives, aims, clients and socio-cultural setting. The practice of extension today according to Akinola, Issa and Sanni (2011), is dissimilar in that the process is dominated by organizations, and its scope has extended from disjointed local events to a complicated, large scale and even worldwide activity. S -Significant at P < 0.05%…”
Section: Factors That Will Increase the Productivity Of Yam Farmers In Rivers And Imo Statesmentioning
confidence: 99%
“…Agricultural extension provides the avenue in which farmers and rural people are helped to improve their desired living conditions through guided farming, processing and marketing of farm products. Agricultural extension system refers to the total framework of extension organizations' action as medium through which educative and problem solving innovations are delivered to the proper audience by a dedicated agent (Akinola, Issa, & Sanni, 2011). It is obvious that the transfer of information and skills has existed and has been undergoing transformation since the emergence of commercial agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…In such regions agricultural development initiatives are essential for the overall rural development process (Islam, 2007;Nadeem and Mushtaq, 2012). Agricultural extension services in these regions serve as an essential tool for economic as well as general rural development (Akinola et al, 2011;Dragić and Živković, 2009). It enhances agricultural production through multiple rural and agricultural development activities (Ifeanyi-Obi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%